SISTEM INFORMASI PERUMAHAN PURIMAS CITRA GEMILANG 2 BERBASIS MOBILE - Arya Gemilang Deva Purwanto; Zainudin Zukhri (STKIP PGRI Situbondo, 2023)
The development of  information technology is increasing rapidly.  Such developments affect  the speed of obtaining information. Unfortunately, there are still many needs for good and comfortable housing that has  not used a good information system to  facilitate housing  management and data collection such as in Purimas Citra Gemilang 2 Housing, a housing that has facilities to meet the needs of its residents.   In managing  housing,  there are often obstacles in terms of data collection management such as monthly contribution payments, registration of  prospective new residents, and recording of housing residents. This is because the recording is still manual.  The use of technology, especially  mobile-based  applications, can  optimize housing implementation  by providing an integrated data management system that can be accessed via smartphones.  Modern housing  needs an application that can support the population system. On that basis,  it is hoped that the application "Housing  Information  System Purimas Citra Gemilang 2 Based on Mobile", can help manage housing more efficiently and effectively. The app's features  are for managing homeowner data,  monthly dues payments, and social  activities.  The stages in the design of this system are analysis,  design, implementation and testing.  The waterfall method  is used in the design of a housing data collection information system.  Housing  residents  can use this system as a means of communication between officers and residents and to assist housing managers  in carrying out social activities and housing data collection.